MEDICAL AND SOCIAL ASPECTS OF BREASTFEEDING - Мельничук, Лариса; Дячук, Анастасія; Боднар, Ірина (SWorldJournal, 2024)
The article is devoted to the study of social and medical factors of breastfeeding. 56 women were surveyed according to the created questionnaire. The questionnaire includes questions about age, social status, health status, compliance with the breastfee